2020
DOI: 10.1001/jamaophthalmol.2019.4796
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Retinal Detachment and Retinoschisis Using Handheld Optical Coherence Tomography in Stage 4 Retinopathy of Prematurity

Abstract: Progression of retinopathy of prematurity (ROP) to stage 4 may require surgical intervention. The partial retinal detachment of stage 4 ROP may involve the fovea (stage 4B ROP) or may not (stage 4A ROP). This determination has heretofore been based on indirect ophthalmoscopy and documented with color fundus photography. OBJECTIVE To investigate optical coherence tomography (OCT) features of eyes with stage 4 ROP and compare them with indirect ophthalmoscopy findings and grading of photographs. DESIGN, SETTING,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…The lack of co‐operation in young children and inability of non‐sedated infants to maintain steady head and eye positions during image acquisition precludes the use of OCT imaging in routine ROP screening. We have previously attempted to use the standard table‐mounted OCT imaging in an anaesthetized child, and faced considerable challenges in head positioning (Harris et al 2009), an issue that has been overcome in centres with access to hand‐held OCT probes (Joshi et al 2006; Chavala et al, 2009; Muni et al 2010; Vinekar et al 2010; Chen et al 2019). However, most studies have relied on OCT image acquisition in infants in supine position in operating theatres under general anaesthesia, where the risks of anaesthesia to premature infants remain substantial and preclude from frequent examination and monitoring of disease progression.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The lack of co‐operation in young children and inability of non‐sedated infants to maintain steady head and eye positions during image acquisition precludes the use of OCT imaging in routine ROP screening. We have previously attempted to use the standard table‐mounted OCT imaging in an anaesthetized child, and faced considerable challenges in head positioning (Harris et al 2009), an issue that has been overcome in centres with access to hand‐held OCT probes (Joshi et al 2006; Chavala et al, 2009; Muni et al 2010; Vinekar et al 2010; Chen et al 2019). However, most studies have relied on OCT image acquisition in infants in supine position in operating theatres under general anaesthesia, where the risks of anaesthesia to premature infants remain substantial and preclude from frequent examination and monitoring of disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, there is currently lack of anatomical data necessary to understand the prevalence and natural history of schitic changes in ROP, which have to date not been easily visible clinically. A recent retrospective review of OCT images revealed the presence of retinoschisis without detachment in 50% of eyes with stage 4a ROP, where decision to operate remained unchanged at the time of examination under anaesthesia (Chen et al 2019). In our prospective case series, the use of SD‐OCT was critical in aiding the diagnosis and subsequent management of all three infants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HH-OCT/OCT-A systems can reliably visualize and measure vitreous opacities and bands, perifoveal vessels, the macular shape, anterior chamber features, retinal tumors, and ganglion cell complex (GCC)/IPL/RNFL thickness in both premature and full-term infants (120)(121)(122)(123)(124)(125)(126)(127)(128)(129)(130). Hence, they are useful in conditions, such as congenital and pediatric glaucoma, macular edema, macular hole, epiretinal membrane, retinoschisis, retinal dystrophies, and other conditions (128,129,(131)(132)(133). Some measurements obtained, mostly from the fovea, could potentially be used to screen for conditions like ROP (132).…”
Section: Handheld Optical Coherence Tomographymentioning
confidence: 99%